The Main Directions of Improving the System of Higher Education in Uzbekistan - ABDURASHIDOVNA, MUKHITDINOVA FIRYUZA; ELIZAVETA, KUTIBAEVA (The journal of contemporary issues in business and government, 2021)
The article deals with organizational and regulatory aspects of the functioning of the higher education system of the Republic of Uzbekistan, the author defines the main stages of development of the higher education system of Uzbekistan and new target settings. The article analyzes the system of higher education in Uzbekistan: issues of quality and efficiency, as well as the main directions of improving the system of higher education at the present stage. The ongoing reforms and prerequisites for improving the higher education system are studied.